DNA damage and cytotoxicity in adult subjects with prediabetes - Pereira, Camila Schreiner; Molz, Patrícia; Palazzo, Roberta Passos; de Freitas, Thiago Aley Brites; Maluf, Sharbel Weidner; Horta, Jorge André; Prá, Daniel; Franke, Silvia Isabel Rech (Mutation research, 2013)
► Nucleoplasmic bridges, but not micronuclei correlated with glycosylated hemoglobin. ► Apoptosis and necrosis correlated with glycosylated hemoglobin. ► Cell death and DNA damage is observed in blood lymphocytes during the initial stages of diabetes. Prediabetes (intermediate hyperglycemia) is a high-risk state for diabetes that is defined by higher than normal glycemic levels that are below the level required for a diagnosis of diabetes. Prediabetes is characterized by oxidative stress, yet the associated DNA damage and cytotoxicity remain unknown to date. Therefore, we evaluated the relationship between glycemic alterations, DNA damage and cytotoxicity in the lymphocytes of individuals with pre-diabetes. Fasting plasma glucose (FPG) and glycated hemoglobin (A1C) levels were quantified and used as inclusion criteria. Anthropometric parameters were also evaluated. The cytokinesis-block micronucleus cytome assay (CBMN Cyt) was used to evaluate DNA damage and cytotoxicity. FPG correlated with A1C (r=0.562, p=0.002). Because A1C is the best predictor of diabetes complications, the association between A1C and the evaluated variables was assessed. The waist–hip ratio correlated with A1C (p<0.01). Regarding DNA damage, the frequency of nucleoplasmic bridges correlated with A1C (p<0.05). Both apoptosis and necrosis correlated with A1C (p<0.05). The overall frequency of DNA damage and cytotoxicity also correlated with A1C (p<0.01). Additional studies evaluating cell cycle and cell death patterns in prediabetes are necessary.